The Role of Observed Punishment in Deterring the Spillover Effects of Corporate Misconduct Among Non‐Peers - HOLZMAN, ERIC R.; MILLER, BRIAN P.; RENNEKAMP, KRISTINA M.; SAUCIUC, ASHLEY K. (Journal of Accounting Research, 2026)
ABSTRACT This study investigates (1) whether misreporting by corporate executives impacts unethical decision‐making by non‐peers in unrelated reporting tasks, and (2) whether observing various forms of punishment for corporate misreporting deters this spillover effect. Specifically, we examine the deterrent effects of two common forms of punishment (fines or imprisonment) and a novel form of punishment (public shaming). Across two experiments, we find that participants are more likely to misreport performance when exposed to media reports about executives engaging in financial misreporting. This evidence is consistent with executive misreporting leading to unethical decision‐making among non‐peer observers. We also find that participant misreporting is reduced when the media reports the punishments levied against those executives. In further mediation tests, our findings suggest observed punishments for corporate misconduct can influence perceptions of injunctive norms and potentially mitigate spillover in unethical behavior.